Suicide mortality after a nonfatal suicide attempt: A systematic review and meta-analysis. (June 2022) - Demesmaeker, Alice; Chazard, Emmanuel; Hoang, Aline; Vaiva, Guillaume; Amad, Ali
Introduction: Deliberate self-harm and suicide attempts share common risk factors but are associated with different epidemiological features. While the rate of suicide after deliberate self-harm has been evaluated in meta-analyses, the specific rate of death by suicide after a previous suicide attempt has never been assessed. The aim of our study was to estimate the incidence of death by suicide after a nonfatal suicide attempt. Method: We developed and followed a standard meta-analysis protocol (systematic review registration—PROSPERO 2021: CRD42021221111). Randomized controlled trials and cohort studies published between 1970 and 2020 focusing on the rate of suicide after suicide attempt were identified in PubMed, PsycInfo and Scopus and qualitatively described. The rates of deaths by suicide at 1, 5 and 10 years after a nonfatal suicide attempt were pooled in a meta-analysis using a random-effects model. Subgroup analysis and meta-regressions were also performed. Results: Our meta-analysis is based on 41 studies. The suicide rate after a nonfatal suicide attempt was 2.8% (2.2–3.5) at 1 year, 5.6% (3.9–7.9) at 5 years and 7.4% (5.2–10.4) at 10 years. Estimates of the suicide rate vary widely depending on the psychiatric diagnosis, the method used for the suicide attempt, the type of study and the age group considered. Conclusion: The evidence of a high rate of suicide deaths in the year following nonfatal suicide attempts should prompt prevention systems to be particularly vigilant during this period.